Computer simulation of the blood flow in a planar configuration for a pulsatile ventricular assist device - Fries, E. (2015)
Patients that suffer congestive cardiac insuffi-ciency need to be assisted with assist devices (VAD) as a tem-poral solution when the cardiac transplantation is not possible. For that reason it is of great interest to know the performance of such devices, especially the potential blood damage that they can produce. In this work, a computational two-dimensional simulation of a novel pulsatile VAD is performed. This new design of VAD has a double acting piston driven electromagnetically at 2.1 Hz. In addition, the VAD has four active valves. The flow velocities, the pressure and the shear stress developed in the blood are analyzed in the chambers and inflow and outflow conduits. The results suggest that the developed flow would not be dangerous for the blood.